A data control framework for SAF-T reporting: A process-based approach - Jerzy Auksztol; Magdalena Chomuszko (Journal of Entrepreneurship, Management and Innovation)
We present an innovative process-based approach aimed at helping entrepreneurs to adapt to the new circumstances arising from the introduction of the Standard Audit File for Tax (SAF-T), which is changing the paradigm of tax authorities3 in dealing with tax non-compliance. The responsibility to protect against evaders has shifted significantly from tax administration towards entrepreneurs, increasing the risk of financial penalties and torts. Simultaneously, it has enabled the introduction of innovative management concepts in the field of financial inspection, auditing, and tax compliance. A process-based approach has been proposed to cope with the complex challenges the entrepreneurs and accountants are now facing in this subject. It is used as a framework for combining key management concepts, like due diligence and quality management, which are typically applied separately. We have achieved our goal by constructing a Data Control Framework (DCF) for SAF-T that addresses the need for the redesign of internal financial control procedures to meet the new requirements of a fiscal audit. Two research methods have been used in this paper: (1) a survey to assess the effects of the implementation of the SAF-T standard in the enterprise and (2) design science research (DSR) for building the proposed framework.